(untitled) (Journal of Engineering, 2018)
The contemporary ideas were characterized by the abundance and diversity of their knowledge, human and conceptual production, the strategy is both a general and a detailed framework covering all design disciplines both inside and outside the field of architecture. From here, many of these terraces emerged from fields outside the field of architecture, but soon moved to form an important nerve within the field of architecture. Hence the need to define a more comprehensive framework for studying one of the concepts that can frame the framework, namely the concept of "Alliteration", and its adoption as an architectural design strategy aimed at giving the resulting form a feature of rhetoric. So the research highlighted the "scientific need to clarify knowledge about the concept of alliteration as a strategy in the design process". The aim of the research is to "clarify the knowledge about the concept of alliteration as a strategy in the design process and to reveal its mechanisms through which it can reach a contemporary architectural form characterized by rhetoric. The research approach represents several procedures to achieve the goal of research and solving the problem of research through the construction of a theoretical framework and the development of the main and secondary vocabulary after the introduction of previous cognitive studies to the selection of samples for application, then discuss, analyze the results and conclusions. Which explained that the strategy of the alliteration enables the reading of the text of the architect within the objectives of both the designer and the recipient of the product, by combining similar systems in form and content, and the integration of properties, reducing the number of words and expand their participation of recipients as a result of reliance on subjective references within the field of architecture.